Contextual Learning Models In PKN Learning - Fitri, Nur Laily; Nasution, Saidatul Fadhillah; Nasution, Abdul Gani Jamora (IKAMAS: Manajemen Pendidikan Islam, 2023)
Citizenship education (civic education) in Indonesia is placed as a field of study that carries a national mission to educate the life of the Indonesian people through the corridor of "value-based education". Civics as a compulsory subject at the school level has a vision as a means of fostering national character (nation and character building) and empowering citizens, and carrying out the mission of forming good citizens, namely citizens who are able to carry out their rights and obligations in the life of the nation and state, in accordance with Pancasila and the 1945 Constitution. In carrying out its mission, Civic Education develops civic competence which includes civic knowledge, civic skills, and civic disposition